2004
DOI: 10.1046/j.8755-8920.2003.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cytokine Concentrations (FGF, sICAM‐1 and SCF) in Serum, Follicular Fluid and ICSI Outcome

Abstract: The concentration of FGF, sICAM-1, and SCF did not differ significantly between the two groups in serum or in FF. Besides, the ICSI outcome was not related to their concentrations in serum or FF. Therefore, these parameters could not be used as a prognostic factor in ICSI program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 42 publications
1
10
1
Order By: Relevance
“…However, treatment of preovulatory oocytes with KITL did not improve the developmental capacity of mouse oocytes. Our data is consistent with previous findings demonstrating that the concentrations of KITL in the human follicular fluid did not associate with the fertilization rate and pregnant outcome in patients undergoing intracytoplasmic sperm injection [ 21 ]. Thus, the processes of nuclear and cytoplasmic maturation of the oocyte are independently regulated and could be controlled by different paracrine factors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, treatment of preovulatory oocytes with KITL did not improve the developmental capacity of mouse oocytes. Our data is consistent with previous findings demonstrating that the concentrations of KITL in the human follicular fluid did not associate with the fertilization rate and pregnant outcome in patients undergoing intracytoplasmic sperm injection [ 21 ]. Thus, the processes of nuclear and cytoplasmic maturation of the oocyte are independently regulated and could be controlled by different paracrine factors.…”
Section: Discussionsupporting
confidence: 93%
“…The dose range of KITL used in the present studies was similar to that used in the rat study[ 26 , 31 ]. Furthermore, the concentrations of KITL in human preovulatory follicular fluid were comparable to those levels[ 21 ]. Similar to the BDNF stimulation of first polar body extrusion, but not GVBD, it is apparent that sequential steps of nuclear maturation of the oocyte are controlled by different paracrine factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of basic FGF did not change in the FF around ovulation in women undergoing ovarian hyperstimulation for IVF therapy and there was no correlation between FF basic FGF levels and reproductive parameters with the exception of age [114]. No correlation could be found between ICSI outcome and FGF concentrations in serum or FF [115].…”
Section: Basic Fibroblast Growth Factormentioning
confidence: 77%
“…Consequently, elevated FF stem cell factor concentrations are associated with an increased likelihood of IVF success [157]. Hammadeh et al [115] found SCF concentrations either in FF or in serum were similar between patients who became pregnant after ICSI and those who did not.…”
Section: Stem Cell Factormentioning
confidence: 99%